Example of teaching practice for the comedy The Cabinet Minister’s Wife by Branislav Nušić - Stanisavljević, Nevena B (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
Awareness of the need for inovation and enrichment curriculum with comedies by Branislav Nušić inspired us to offer a creative methodological model processing for comedy Gospođa ministarka (The Cabinet Minister’s Wife), in order to point out the possibility of it’s involvement in the educational process and the positive effects that such action had. The reason for selecting just this comedy lies in the fact that, despite the fact that it’s title well understood, it’s ideological layer, referring to criticism of the government and power, can positively influence the development of student’s personality traits. Our proposal is to analyze comedy Gospođa ministarka (The Cabinet Minister’s Wife) in the sixth grade, however, such an approach does not cease the possibility of interpretation of a play in teaching practices, but use the offered model as the starting point of any new readings and interpretation in the educational practice.